$L$-INDISTINGUISHABILITY ON EIGENVARIETIES. (22nd March 2016) - Ludwig, Judith
Abstract : In this article, we construct examples of $L$ -indistinguishable overconvergent eigenforms for an inner form of $\text{SL}_{2}$ .